KELAYAKAN EKONOMI USAHATANI ROTAN DI DESA TERANTANG HILIR KECAMATAN BAAMANG KABUPATEN KOTAWARINGIN TIMUR - Marhat Marhat; Mohammad Fadil (Universitas Tribhuwana Tunggadewi, 2009)
East Kotawaringin region is one of the areas, which has been supported natural condition for the growth, and developing of rattan. Habitat of rattan in this area consists of riverside, ex farm, forest, swamp, and underbrush. This research aims to learn the cost, revenue, profit, and economy feasibility of rattan farming. Location of research of purposifely determined in Terantang Hilir Village as one of the villages of rattan developing. The samples are 60 participants. Data is gained from primary and secondary data, by using farming analysis method. Result of research shows, rattan farming cost in Terantang Hilir Village is Rp 11.185.558,47/hectare in average, with in revenue in average of Rp 14.845.358,33/hectare. Revenue cost ration value is 1,32 gives meaning that rattan farming in Terantang Hilir Village, Baamang Area, East Kotawaringin Region, is economically feasible to be developed